Final automatization of calculations in the Geofarmer App to assess farms climate smartness - Andrieu, Nadine; Bonilla Findji, Osana; Eitzinger, Anton (2020)
We describe the last update made in the Geofarm App to assess farms climate smartness. 43 new variables were added to the app and correspond to the calculate cost and benefit, supply and demand of calories, of fodder, of nitrogen, CO2 emissions at crop and animal level.